2021
DOI: 10.1016/j.onehlt.2021.100300
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the source of identified non-foodborne pathogens from food-contact wooden surfaces used in Hong Kong's urban wet markets

Abstract: In this study, a phylogenic analysis was performed on pathogens previously identified in Hong Kong wet markets' cutting boards. Phylogenetic comparisons were made between phylotypes obtained in this study and environmental and clinical phylotypes for establishing the possible origin of selected bacterial species isolated from wet market cutting board ecosystems. The results reveal a strong relationship between wet market bacterial assemblages and environmental and clinically relevant phylotypes. However, our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…(2020), who analyzed the microbial profiles of biofilms on wooden cutting boards from 11 wet markets in Hong Kong and found natural surface presence of V. parahaemolyticus and V. vulnificus , which was later confirmed by Rao et al. (2021). Cutting boards represent hotspots for cross‐contamination ranging from food processing plants to the kitchens of consumers.…”
Section: Contamination Routes Of Processed Seafoodmentioning
confidence: 81%
“…(2020), who analyzed the microbial profiles of biofilms on wooden cutting boards from 11 wet markets in Hong Kong and found natural surface presence of V. parahaemolyticus and V. vulnificus , which was later confirmed by Rao et al. (2021). Cutting boards represent hotspots for cross‐contamination ranging from food processing plants to the kitchens of consumers.…”
Section: Contamination Routes Of Processed Seafoodmentioning
confidence: 81%
“…in seafood can occur in the environment and the periods of carrying or selling to consumers. Moreover, previous studies have reported the contamination of V. cholerae in food related to cross-contamination by seafood storage and handling [34][35][36] . This study revealed that there was the presence of V. cholerae and V. parahaemolyticus in seafood distributed in Mueang Yala, Yala province.…”
Section: Resultsmentioning
confidence: 99%
“…The Codex code of practice for fishery products fails to recognise pathogenic bacteria on the surface of uncooked thawed imported fish as a potential human health hazard. Contamination of hands, cutting surfaces and kitchen utensils prior to cooking is a significant threat and one which has been described in published literature [ 124 , 125 , 126 , 127 , 128 ]. Far from indigenous bacteria occurring in low numbers in the present study, bacteria C. testosteroni , Pseudomonas spp., V. fluvialis and Micrococcus sp.…”
Section: Discussionmentioning
confidence: 99%